Accuracy of orthognathic surgery using 3D computer-assisted surgical simulation - Lee Richard; Goonewardene Mithran S; Mian Ajmal; Allan Brent; Brock Danny; Trevenen Michelle (Sciendo, 2018)
To evaluate the accuracy of maxilla and mandibular repositioning during two-jaw orthognathic surgery using computerassisted surgical simulation (CASS)